Non-surgical organ preservation in laryngeal and hypopharyngeal cancers: an audit from the clinic. Issue 4 (9th April 2023) - Sood, S; Sinha, S; Balaji, A; Mundhe, S R; Mummudi, N; Budrukkar, A; Swain, M; Prabash, K; Noronha, V; Joshi, A; Patil, V; Laskar, S G
Abstract: Background: There is increasing concern regarding efficacy of organ preservation protocol in laryngeal and hypopharyngeal cancers. Method: This study retrospectively assessed disease-related and functional outcomes of 191 patients with non-metastatic laryngeal or hypopharyngeal squamous cell carcinoma treated with curative intent (radiotherapy with or without chemotherapy). Results: Seventy-six patients (39.8 per cent) had a primary cancer in the larynx, and 115 patients (60.2 per cent) had a primary cancer in the hypopharynx. The median follow up was 39 months. The 3-year time to progression, overall survival, local control and laryngectomy free survival was 56.2 per cent, 76.3 per cent, 73.2 per cent and 67.2 per cent, respectively. At the time of analysis, 83 patients (43.5 per cent) were alive and disease free at their last follow up and did not require tube feeding or tracheostomy. The laryngo-oesophageal dysfunction-free survival was 61 per cent at 3 years. Conclusion: Organ conservation protocols remain the standard of treatment in appropriately selected patients with laryngeal and hypopharyngeal cancers.